Study of transmission routes of Helicobacter pylori in relation to seroprevalence of hepatitis A virus. - Furuta, T (1997)
The seroprevalence of Helicobacter pylori in a group of 1,043 healthy Japanese people was compared with that of hepatitis A virus (HAV), which was used as a marker of fecal-oral exposure. No statistically significant relationship was observed between seropositivity for HAV and that for H. pylori. Therefore, the fecal-oral spread of H. pylori is of limited relevance in Japan.